Nuristanske sølvpokaler - Edelberg, Lennart (Kuml, 1965)
MAP OF NURISTAN (Inserted at the end of the volume) The basis of my work has been my own observations in the territory including compass bearings and studies of stereoscopic air photographs (Scale 1:250,000 and 1:25,000), kindly placed at my disposal in August 1964 by the Afghan Ministry of Mines and Industries. I found most useful the air photographs from valleys with which I had become familiar when I visited them myself, viz. Parun-Kantiwo-Pech, Waigal, Netshingal, and Lower Bashgal. But the photographs from the valleys of Upper Bashgal and Skorigul, which I have not visited personally, have also been of the greatest importance to the preciseness of the map. The three dotted lines crossing the Bashgal, Pech and Kushkau rivers denote that the areas of drainage beyond have been drawn on the basis of air photographs scale 1:250,000. An exception to this, however, are the small tributaries whose mouths have been marked by dotted lines; they have been drawn according to my own observations. For Southern Waigal I have availed myself of sketches kindly placed at my disposal by Professor Georg Morgenstierne, who travelled up to Kegal in 1949. For Western Nuristan I have found Schuyler Jones's sketches from Titin and Malil most useful and have otherwise had to rely on material published earlier from the German expedition in 1935 (Deutsche im Hindukusch, Berlin 1937) and from Thesiger's journey in 1956 (Thesiger, W., A Journey in Nuristan. The Geogr. Journ., London 1957). The source of place-names has mainly been my own collections, supplemented by and compared with names as found in Morgenstierne (Morgenstierne, G., The Waigali Language, Oslo 1954, the map p. 258 and the index of geographical names p. 320-323) and in Lentz (Deutsche im Hindukusch 1937). When individual villages and localities are to be named on a map like this, one af the following alternatives may be used: (1) the name used locally, (2) the name used by some Nuristani tribe for localities outside its own territory, (3) the Pashtu version, (4) the Persian version. In the Waigal area I have used local forms, as few of these places, in a region visited by only a very limited number of explorers, have been mentioned to any noticeable degree in the records -in other words: so far there is no other fixed, written tradition. In the other valleys I have been less consistent because in literature dealing with these a tradition has already been created for using non-local names of varying origin. New settlements are continually made in Nuristan in connection with the construction of terraces for new fields. Islamabad as a name for the village that was built instead of Muldesh, destroyed during the conquest, is an example of a name which is not easily accepted. At the original Muldesh (Muldesh 1) there is now a small government office. Future explorers will probably have to move the names of the mountain pastures a little as the exact position of these is gradually determined. Attention is drawn to the fact that there are no areas with perpetual snow in Nuristan although this is often asserted. On most maps Kashmund is put with an altitude approximately 1000 metres too low. Robertson (Robertson, Sir George S., The Kafirs of the Hindu Kush, London 1896) seems to be nearer to the truth when he argues 13,900 feet. The height argued by me was established by means of bearings taken from a place near Wama whose altitude was known to me. Silver Cups of Nuristan "So prevalent is the use of wine among them, that every Kafir has a "khig", or leathern bottle of wine about his neck; they drink wine instead of water." The Grand Mogul Zehir-ed-Din Muhammed Babur A. H. 920 - A. D. 1514. I Nuristan is a fairly well-defined ethnic area in the Hindukush in northeastern Afghanistan. Nuristan means the Land of Light, and the name refers to the bringing of the light of Islam to the heathen population after the Amir of Afghanistan Abdur Rahman had conquered the country in the winter of 1895/96. Previously the surrounding Muslim peoples had called the area Kafiristan, the Land of the Heathen, and this name is still generally used in the scientific literature. The English statesman Mountstuart Elphinstone published in 1815 his famous work "An Account of the Kingdom of Caubul", in which he gives the first careful description of Kafiristan, remarkable for its accuracy in view of the fact that the author had to base his description on second-hand reports. He writes herein that the Kafirs "were celebrated for their beauty and their European complexion, worshipped idols, drank wine in silver cups or vases, used chairs and tables, and spoke a language unknown to their neighbours". Elphinstone goes into greater detail elsewhere in his description: "They all, of both sexes, drink wine to great excess: they have three kinds, red, white, and dark-couloured, besides a sort of the consistence of a jelly, and very strong. They drink wine, both pure and diluted, out of large silver cups, which are the most precious of their possessions. They drink during their meals, and are elevated, but not made quarrelsome, by this indulgence." II-Urei These silver cups had never been seen by Europeans. During a visit in 1948 to the garden Indrakun near the village of Wama I learned that the Kafirs used to assemble after the grape harvest around fermenting vats cut in large rocks, and to drink the newly fermented wine from silver cups. But it was not until 1953 that I succeeded in seeing two specimens in the village of Zhönchigal (urei I and II). They were apparently held in high honour, and I made no attempt to acquire them. In 1954 I heard that in certain places in the Waigal valley area silver cups were being cut up for bracelets. Urged on by this knowledge I acquired two specimens that same year in Amshoz (urei III and IV). Finally I bought a cup (urei V) in Zhönchigal in 1964 and presented it to the Kabul Museum. III-lndrakun On a natural terrace, 150 acres in extent, southwest of Wama lies the garden of lndrakun mentioned above. The garden is sacred to Indra, who established it, and built an irrigation channel which brings water for its use. It was also lndra who had planted the sacred juniper cedar (Juniperus polycarpos C. Koch), bringing it from the mountain pasture of Surmeia. The vines extend from fruit-tree to fruit-tree, and the penalty for plucking the grapes before the harvest was publicly proclaimed was that the offender was cast down from a vertical cliff that forms the edge of the garden towards the Aka valley. See too the text attached to the map of the garden. IV-Drasletr To this day the grape harvest is still preceded by a public preliminary, and it is still punishable to pluck grapes -even ones own- before this commencing ceremony. It is the "alderman" of the craftsmen who the previous evening proclaims from the roof of the mosque or some other prominent place in the village that the harvest may begin the following day. In Zhönchigal the month of the grape harvest is called Taraskando, and this name is clearly associated with the god Taraskan, who corresponds to lndra. Until the beginning of the grape harvest specially selected members of the community called urei- keep watch to ensure that none steals grapes. The grapes are nowadays eaten fresh, while a substance is also met with consisting of dried and pressed grapes. This substance was also known in heathen times, whereas raisins are, and were, unknown in Nuristan. V-Wine and Soma Among the Aryan pastoralists was found an intoxicating immortality-drink which is called in the Rigveda soma -a name also applied to the plant from which the drink was made. Soma was moreover regarded as a divinity. Aurel Stein -and Roth before him- considered that the soma-plant could be identified as rhubarb. Georg Morgenstierne has shown how one of the epithets which the Veda epics used of the soma plant probably survives to this day among the people of Nuristan. This is the kati word cәwō and the paruni word ucapәr, both of which mean rhubarb and both of which appear to be derived from the Veda word slvātrá, meaning "invigorating". It is said to be possible to produce an intoxicating drink from milk and the juice of pressed rhubarb stalks, the milk-sugar providing the necessary ingredient for the fermenting process. We have, however, no record of such a drink in Kafiristan or Nuristan, although the rhubarb plant is commonly found on the Nuristani mountain pastures around the higher chalets. Among the Aryans lndra was closely associated with the soma: Rigveda VIII, 48 reads: "O Soma, may you rejoice together with Indra", and Rigveda I, 32, commencing with: "I will praise the heroic deeds of Indra ... ", goes on to say: "Rutting like a bull he demanded soma to drink; three bowls full he emptied the juice." Such lines give food for speculation to one who has wandered in lndrakun, Wama's garden. And when one has traced the watercourse, superb by Nuristani standards, which lndra carved out of the mountain-side to lead water to his garden, one is not surprised, later in the hymn, to read: "The hole of the waters was closed; this Indra opened, when he conquered Vritra" (he drought-demon). The use of grape wine instead of rhubarb wine in the ritual of the Kafirs may -as Morgenstierne says- be an innovation, though possibly a quite early one. For how long, then, has grape wine been produced in Kafiristan? Let us ask the ancient writers, and see if we receive an answer. From before the time of Alexander the Great nothing appears to have survived in literature concerning the peoples of these regions, and unfortunately only few and scattered fragments remain of the works of the historians who themselves took part in his campaign. Nor does it help, that Alexander caused his official historian, Kallisthenes, who accompanied him, to be imprisoned, and perhaps executed -an event which appears to have taken place near the Hindukush. Not until Curtius Rufus (probably about A.D. 50) and Arrian (about A.D. 100) have we narratives, and they are a good 300 years later than the events they describe. Curtius Rufus writes: " ... When he (Alexander) thereafter had conquered an unknown people, he came to the city of Nysa. By chance the camp was pitched in a wooded area close by the walls. The cold of the night attacked the men unusually severely, and here there was fuel enough to hand with which to make fire. So they forthwith made inroads on the forest and set alight to the trees; and the fire, thus nourished, attacked the burial places of the inhabitants. These ancient buildings, being made of cedar wood, easily caught fire and the fire spread to all sides ... " " ... Finally, tiring of the misfortunes of the siege, they (the inhabitants) surrendered. They said that their city had been founded by Father Bacchus ... The city Iies at the foot of a mountain, which the inhabitants called Meros ... A large quantity of ivy and vines grows everywhere on the mountain, and here are many springs. Here are also fruit-trees of varied and nourishing taste, the earth of itself producing fruit from chance-planted seed. Laurel and olive trees, and an extensive forest of wild trees, are found on these cliffs." Curtius Rufus goes on to tell how Alexander's soldiers become gradually more and more frivolous, garland themselves with ivy and vines, and with the king's approval abandon themselves to feasting and wine. Arrian, in his book, causes King Akufis from the besieged Nysa to address Alexander as follows: " ... Let this thing too serve you as a proof that our city was founded by Dionysos, that ivy, which grows no other place in the land of the Indians, grows here among us." And later: "Alexander was also desirous of seeing the place where there were, according to the proud boast of the men of Nysa, certain memorials of Dionysos. He therefore went, it is said, to the mountain of Meros ... and there he saw that the mountain was full of ivy and laurel, and thickly clothed with many other kinds of shady forest trees, and that there was possibility there for hunting of all kinds of game. The Macedonians were glad when they saw the ivy, for they had not seen it for a long time (for there was no ivy in the land of the Persians, not even there where they had vines); and they eagerly made garlands of it and garlanded themselves on the spot, while they sang hymns in praise of Dionysos and called upon the god by his various epithets. There, too, Alexander sacrificed to Dionysos and held a sumptuous banquet together with his boon companions. Some authorities have even told in their writings (if one can believe them) that many of the most prominent of the Macedonians in his following, while crowned with ivy and calling upon Dionysos, became possessed by the god and celebrated his worship with cries of Evoi and Bacchic frenzies." In his work "Concerning India" Arrian writes finally: " ... According to a widespread legend Dionysos also, before Alexander, campaigned against the people of India ... As regards Dionysos and his campaign, there exists a monument of no little importance to this both in the city of Nysa and on the mountain of Meros, and in the ivy which grows only on that mountain ... " Thus the ancients. In the passages here quoted the following plants are mentioned: 1. Vine -concerning which it can be said that in its cultivated form it is today found extensively throughout the whole of Persia and Afghanistan. In its wild form I have found it in Nuristan and Luristan (the Zagros mountains in Iran) -in both regions associated with woods of evergreen oak, Quercus Balout. 2. Ivy is found within the frontiers of Afghanistan only in Nuristan (Wama, Kurder, the Waigal valley). As a curiosity I may add that the author of the commentaries to Apollonios's Argonautica, verses 904-907, writes that Kleitarchos -in connection with his description of Nysa- mentions that a plant resembling ivy, which grows there, is called "skindapsos." For possible use in comparison I have collected the following local names for ivy in Nuristan: Wama: "prozә"; Zhönchigal: "pēzwah"; Kurder: "balašәn." 3. Cedar is found within Afghanistan only in Nuristan and in the Gardez region in the province of Junubi. 4. Laurel was called Daphne by the Greeks. It was probably of the species D. Laureola L. In Nuristan, the neighbouring Nijrao and in Baluchistan the species D. Augustifolia is found. 5. Olive is found in its wild form in Nuristan and is probably not widespread outside that region. However, it should be noted that in the text quoted Rufus merely writes "lauri baccaeque", which should probably not be translated "laurel and olive" but "laurels" only. Thus the first region where a traveller from the west can find all the plants mentioned together is -so far as my botanical knowledge goes- Nuristan. As we know that Alexander was in Nysa before he came to Aornos, which has been identified by Sir Aurel Stein as situated in Swat in the northern part of West-Pakistan, we may assume from the botanical criteria that Nysa must have lain in the border area of Kafiristan. To this may be added that over the greater part of Afghanistan burial places are underground, but precisely in Kafiristan the dead were laid in four-legged coffins of cedar-wood which were set up in cemeteries outside the towns, and to this day "houses" of cedar are built above the burial places of prominent people in Wama and the Waigal valley (fig. 22). There thus appears to be good reason to believe that the people whom Alexander met with at the "mountain of Meros" were the cultural forefathers of the Kafirs, and that the wine-cult there thus goes back to before 326 B.C. But the forefathers of the "people of Nysa" may well have been soma-drinkers, and the connection between lndra and that intoxicating drink would seem almost to point in that direction. 17-1800 years were to pass before, with Tamerlane and Babur, we again hear of the Kafirs' wine production; and it is not until 1815 that we read in Elphinstone of the silver cups. In addition to the account mentioned earlier he also relates that a Kafir bride is "led out with a basket on her back containing fruits and walnuts prepared with honey, and (if the family can afford it) a silver cup". Burnes claims (1838) that these silver cups are trophies of their spoil in war, and for that matter there is presumably nothing to prevent the Kafirs, during their continual internal warfare, from having plundered them from each other. One would, however, in that case have expected that the greatest number of cups would have been found among the strongest tribe in Kafiristan, the Kam people in lower Bashgal; but G. S. Robertson, who spent a whole year (1890-91) in Kamdesh, apparently never saw nor heard of the silver cups. Nor is it easy to imagine how people living in Wama or the Waigal valley could have taken such objects as plunder from the surrounding Muslims, who never drank wine. I am therefore of the opinion that the silver cups were homemade, wrought by the craftsmen of Kafiristan, the so-called bari, and possibly only by bari in Wama, Ashkun (?) and the Waigal valley. In Burnes's day -as in Alexander's- the Kafirs were fully conscious that their winedrinking was something distinctive. One of his Kafir informants assured him that his tribe looked upon all as brothers, who wore ringlets and drank wine. In the years 1889 and 1890-91 G. S. Robertson, as told above, lived in Kafiristan, and he was the first to publish personal first-hand experiences in his large work "The Kafirs of the Hindu Kush." He was at the same time the last westener to visit Kafiristan before its conquest in 1895-96. His book is therefore the main authority in all Kafiristan research. But, as said above, he knows nothing of the silver cups. Unless indeed certain "shallow tin bowls", which Robertson saw wine being served in, can in reality have been cups of sheet silver. Robertson is the only westener who has seen the Kafirs press grapes for wine. It occurred in the Bashgal valley in the little village of Bináram a little to the south of Kamdesh. The pressing vat was not so elaborate as the one in lndrakun, which, as we have described, was carved from a single block of stone which also contained a smaller vat to receive the grape-juice. At Bináram the pressing vat was built up of large and small stones, with the interstices filled with clay. The walls were about 2½ feet high, and the vat measured 5½ by 4 feet. At one end of the vat, at the bottom, there was a tapping hole, which was blocked with a handful of twigs and from which projected a spout or gutter of wood, below which wooden vessels were set. A woman emptied at intervals baskets of freshly plucked grapes into the pressing vat. A large and powerful man had been selected by the owner to press the grapes and with that in view had his feet washed first. The grape-juice which flowed from the vat was poured back into the vat by means of the wooden vessels, and was thereafter poured into goatskins by means of a wooden funnel. Robertson mentions that the sweet grape-juice in the goatskins tasted excellent. But after eight to ten days it became sour through fermentation, and has thus become wine. The wine was not strained, and the liquid looked unappetizing. The Kafirs always blew into the wine-bowl before they drank, perhaps "to remove the scum from near their lips". The wine was thin, but was nevertheless normally diluted with water. However, the wine which was allowed to stand for two or three years became clear and occasionally considerably stronger. Robertson writes, that some Europeans liked the ordinary Kafir wine, a remarkable statement as there are no records of wine ever having been exported from Kafiristan; but perhaps by Europeans he is referring to W. Lockhart's military mission of 1885-86 which reached the Bashgal valley. Robertson records in addition that he never saw a Kafir drunk. He finally describes how the juice is pressed out of the remains of the grapes in the vat by placing the mish between stones and using a bar as a lever. This vat-residue is then dried and formed into small cakes which, according to Robertson, tasted most unpleasant. But the Kafirs valued this by-product and considered it highly sustaining. According to Robertson, the most usual occasions on which wine was drunk were definitely the mourning and dancing ceremonies which were held on the occasion of a death, particularly a death in battle. On such occasions a figure was sometimes constructed of grass, to represent the departed. This figure was brought to the dancing-house, whereupon the relatives of the dead man would distribute wine and food, to the accompaniment of tears, speeches and dances. Among modern authors who have described the wine production of the Kafirs Safar Wakil Gharzai deserves a hearing, since he is himself a Nuristani. He writes, that the Kafirs could make wooden vats, so large that five men could stand in them during the pressing, and that both men and women took part in this work. They washed themselves and put on new clothes for the work. At the bottom of the pressing vat there was a special hole for tapping, and in this hole a plant was placed called suma, according to Safar Wakil a Kafir word. The grape-juice was poured into pottery jars which were stored in the cellar after they had been fitted with lids. The grape harvest was a particularly festive season, according to Safar Wakil. Boys and girls sang in rotation, and both men and women drank. If a woman bore a child during the grape harvest one of the winejars was given the child's name, and its contents were set aside until the child's wedding. Safar Wakil lists the towns where wine was made, and according to his list wine production was known as far to the west as Anish in the Alingar valley region. Finally he mentions the silver cups, adding that every man had his own silver cup, and that the bride's father used to give the bride a cup to take with her on her journey to the bridegroom's house. VI-Trapei At the Kabul Museum there has for years stood a three-legged table with an odd side-stand of unknown significance. In Zhönchigal they showed me that the silver cup had its place here during the meals. Kafirs of rank had the privilege of sitting on a chair with a back-rest, the so-called horn-chair. With a little imagination we can picture him on his carved chair, eating his meal from the ornamented bowl on the three-legged table, while his silver cup, filled with wine, rests in the special holder. All three things, however, in addition to bearing witness to the standing of the owner, also testify to the skill and fertile imagination of the craftsman, a skill which still shows itself in the beautiful architectural features of Nuristan, where both mosques and private houses are often decorated with splendid carvings. Lennart Edelberg.